Number Conservation is Related to Children’s Prefrontal Inhibitory Control: An fMRI Study of a Piagetian Task - Poirel, Nicolas (Public Library of Science, 2012)
Although young children can accurately determine that two rows contain the same number of coins when they are placed in a one-to-one correspondence, children younger than 7 years of age erroneously think that the longer row contains more coins when the coins in one of the rows are spread apart. To demonstrate that prefrontal inhibitory control is necessary to succeed at this task (Piaget’s conservation-of-number task), we studied the relationship between the percentage of BOLD signal changes in the brain areas activated in this developmental task and behavioral performance on a Stroop task and a Backward Digit Span task. The level of activation in the right insula/inferior frontal gyrus was selectively related to inhibitory control efficiency (i.e., the Stroop task), whereas the activation in the left intraparietal sulcus (IPS) was selectively related to the ability to manipulate numerical information in working memory (i.e., the Backward Digit Span task). Taken together, the results indicate that to acquire number conservation, children’s brains must not only activate the reversibility of cognitive operations (supported by the IPS) but also inhibit a misleading length-equal-number strategy (supported by the right insula/inferior frontal gyrus).